Prarancangan Pabrik Metil Ester Dari Minyak Jarak Pagar Dan Metanol Kapasitas 70.000 Ton/Tahun - Sulistyaningsih, Ratri; , Tri Widayatno ST., M.Sc., Ph.D; , Ir. Haryanto AR. MS (2016)
Indonesia is one country with oil producers in the world, but is still importing fuel oil (BBM) for sufficient fuel in the transport and energy sectors. One effort to reduce the amount of imports and overcome the dependence on fossil fuels then established factory Methyl Ester of castor oil and methanol with a capacity of 70,000 tons / year will be built in Gresik, East Java operated for 330 days /year. The process of making Methyl Ester done by a ransesterification process is carried out in a flow reactor stirred tank. In the reactor the reaction at liquid-liquid phase mole ratio of castor oil with methanol 1: 6. The reactions are reversible, exothermic with non-adiabatic isothermal conditions at 60 ° C and at a pressure of 1 atm. This plant is classified as a low risk operating at atmospheric pressure conditions. Raw material requirements Jatropha Oil of 8882.30 kg / h and methanol amounted to 1912.14 kg / hour. NaOH supporting materials amounted to 266.47 kg / hour. Methyl Ester product in the form of 8838.38 kg / hour. Support utilities includes supplying process water extracted from the river at 18436.70 kg / hour and the supply of saturated steam at 55282.63 kg / h obtained from the boiler with diesel fuel amounted to 52.67 liters / hour, demand for electricity is obtained from the PLN and generator set of 400 kW. The factory was stablished industrial region, Gresik, East Java, with a land area of 20,000 m2 and the number of employees 154 people. Methyl Ester factory founded by Rp.437.943.991.999 need capital and working capital of Rp 161 044 388 332. From the economic analysis of this plant demonstrates a pretax profit Rp.130.768.256.995 /year after taxes 30% profit reached Rp 91,537,781,996 /year. Percent Return On Investment (ROI) before tax after tax 29.86% and 20.90%. Pay Out Time (POT) before tax for 2.5 years and 3.2 years after tax. Break Even Time (BEP) amounted to 51.68%, and Shut Down Point (SDP) amounted to 27.72%. Discounted Cash Flow (DCF) accounted for 39.77%. From the data above feasibility analysis concluded that the plant is profitable and feasible to set. Keywords: Jatropha oil, transesterification, methanol